2006
DOI: 10.2147/copd.2006.1.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of chronic obstructive pulmonary disease

Abstract: None of the drugs currently available for chronic obstructive pulmonary disease (COPD) are able to reduce the progressive decline in lung function which is the hallmark of this disease. Smoking cessation is the only intervention that has proved effective. The current pharmacological treatment of COPD is symptomatic and is mainly based on bronchodilators, such as selective β2-adrenergic agonists (short- and long-acting), anticholinergics, theophylline, or a combination of these drugs. Glucocorticoids are not ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 115 publications
(178 reference statements)
2
36
0
Order By: Relevance
“…These long-acting bronchodilators have a significantly positive effect on FEV1, lung volumes, dyspnea, exacerbation rate and quality of life [12][13][14][15][16] . Since inflammation in patients with COPD is, at least partly, corticosteroid-resistant, due to a reduced activity of the histone deacetylase the use of glucocorticosteroids (GCs) remains controversial 10,12,[16][17][18][19][20][21] . However, this treatment is recommended for moderate/severe COPD rather than mild COPD since there is no other therapeutic option 10,13 .…”
Section: New Drug Developments In Copdmentioning
confidence: 99%
See 4 more Smart Citations
“…These long-acting bronchodilators have a significantly positive effect on FEV1, lung volumes, dyspnea, exacerbation rate and quality of life [12][13][14][15][16] . Since inflammation in patients with COPD is, at least partly, corticosteroid-resistant, due to a reduced activity of the histone deacetylase the use of glucocorticosteroids (GCs) remains controversial 10,12,[16][17][18][19][20][21] . However, this treatment is recommended for moderate/severe COPD rather than mild COPD since there is no other therapeutic option 10,13 .…”
Section: New Drug Developments In Copdmentioning
confidence: 99%
“…However, this treatment is recommended for moderate/severe COPD rather than mild COPD since there is no other therapeutic option 10,13 . A large clinical trial has shown improvements in lung function, and decreased exacerbation frequency in individuals receiving combined inhaled GC and LABA treatment versus placebo and oral GC therapy is also recommended for the treatment of COPD exacerbations [10][11][12][13][18][19][20][21] . The use of theophyllines has been associated with a reduction in the rate of COPD exacerbations compared with long-acting β2-agonists among COPD patients.…”
Section: New Drug Developments In Copdmentioning
confidence: 99%
See 3 more Smart Citations